Increasing Madrasah Aliyah Teacher Creativity through Madrasah Principal Leadership, Madrasah Climate, and Scientific Literacy - Yuliani, Rini Dwi; Azainil, Azainil; Mulawarman, Widyatmike Gede (Magister Manajemen Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2024)
This research aims to examine the leadership of madrasah heads, madrasah climate, and scientific literacy that can encourage and have a positive influence on teacher creativity at Madrasah Aliyah. Teacher creativity plays an important role in the success of the learning process, influenced by several factors such as leadership support from the madrasah head, the madrasa environment, and strong scientific literacy. This research uses a quantitative approach with a survey design, data collection is carried out through questionnaires distributed to Madrasah Aliyah teachers. Research findings reveal that the leadership of madrasah heads has a significant positive effect on teacher creativity, encouraging the exploration of new ideas and the development of creativity. Apart from that, the supportive madrasah climate encourages teacher creativity in the learning process. Scientific literacy helps teachers in designing and delivering learning with scientific knowledge. The research concluded that these three factors interact with each other and are essential in increasing teacher creativity at Madrasah Aliyah. Therefore, support from the leadership of the madrasah head, a conducive madrasah climate, and increasing scientific literacy are the keys to increasing teacher creativity in education at the Madrasah Aliyah level.